2016
DOI: 10.1038/srep23464
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C virus NS5A protein cooperates with phosphatidylinositol 4-kinase IIIα to induce mitochondrial fragmentation

Abstract: Hepatitis C virus (HCV) has long been observed to take advantage of the host mitochondria to support viral replication and assembly. The HCV core protein has been implicated to fragment host mitochondria. In this report, we have discovered that the non-structural protein 5A (NS5A) plays an instructive role in attaching ER with mitochondria, causing mitochondrial fragmentation. Dynamin-related protein 1(Drp1), a host protein essential to mitochondrial membrane fission, does not play a role in NS5A-induced mitoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 38 publications
1
16
0
Order By: Relevance
“…NS5A prevented the activation of the caspase-3, presumably through the inhibition of caspase-9. Notably, this is in agreement with the literature data, as this protein was shown earlier to use multiple strategies to block inner pathways of apoptosis by interfering with various host factors [ 8 , 9 , 41 ]. Since the inner pathway of apoptosis is activated through mitochondrial dysfunction, the reason why NS5A did not induce it while the HCV core did does not seem obvious; both of them triggered the massive production of ROS [ 42 , 43 ].…”
Section: Discussionsupporting
confidence: 92%
“…NS5A prevented the activation of the caspase-3, presumably through the inhibition of caspase-9. Notably, this is in agreement with the literature data, as this protein was shown earlier to use multiple strategies to block inner pathways of apoptosis by interfering with various host factors [ 8 , 9 , 41 ]. Since the inner pathway of apoptosis is activated through mitochondrial dysfunction, the reason why NS5A did not induce it while the HCV core did does not seem obvious; both of them triggered the massive production of ROS [ 42 , 43 ].…”
Section: Discussionsupporting
confidence: 92%
“…In contrast to these findings, two other studies have reported DENV-induced mitochondrial fragmentation that is mediated by mitofusin degradation 152,153 . These studies suggest a mechanism similar to HCV in which virus-induced mitochondrial fission inhibits apoptosis and alleviates immune activation 118,154 . The differences between these reported observations could arise from differences in experimental setup or host cells that were used for infection.…”
Section: Mitochondriamentioning
confidence: 92%
“…In the case of HCV, viral proteins are enriched on mitochondria and MAMs, and viral infection promotes mitochondrial fragmentation and mitophagy 118,154,155 (FIG. 4).…”
Section: Mitochondriamentioning
confidence: 99%
“…It has been found to interact with numerous cellular pathways via its conserved polyprotein cluster [8], which matches the Src homology 3 binding motif of many signaling molecules [9]. Interestingly, NS5A has recently been reported to induce mitochondrial fragmentation [10], which is important for the induction of mitophagy.…”
Section: Introductionmentioning
confidence: 99%